Consanguinity and the Risk of Hashimoto's Thyroiditis - Zaghlol, Raja Y; Haghighi, Alireza; Alkhayyat, Motasem M; Theyab, Othman F; Owaydah, Amal M; Massad, Mu'taz M; Atari, Mohammad A; Zayed, Ayman A (Thyroid (New York, N.Y.), 2017)
Hashimoto's thyroiditis (HT) is the most common autoimmune thyroid disease that may lead to hypothyroidism due to progressive destruction of the thyroid. The etiology of HT is unclear. However, it is associated with multiple genetic predispositions. Consanguinity has been associated with an increased susceptibility to different inherited conditions. This study investigated the association between consanguinity and risk of HT for the first time. Using a case-control study design, 298 HT patients were compared with two subject groups: (i) 299 participants with non-HT hypothyroidism, and (ii) 298 healthy control participants. The three groups were age and sex matched. Presence of consanguinity among the parents was compared in these groups, and odds ratios (OR) were calculated to establish a correlation. Consanguinity significantly increased the risk of HT (compared with healthy subjects; OR = 3.3; p < 0.0001). In addition, consanguinity was a significant risk factor for HT compared with non-HT hypothyroidism patients (OR = 2.8; p < 0.0001). However, the prevalence of consanguinity was not significantly different in non-HT hypothyroidism patients and healthy subjects. The results suggest that the risk for HT is increased in consanguineous unions, but no significant increase in the risk of non-HT hypothyroidism was observed. However, for more precise risk estimates, larger studies that include different populations may be helpful. These findings highlight the health impact of consanguinity and have applications in empiric risk estimations in genetic counseling, particularly in countries with high rates of consanguineous marriages.